Vaccine Information Seeking Behavior Among Pregnant Women in Khartoum State, Sudan: A Hospital-Based Cross-Sectional Study - Sabahelzain, Majdi M.; Ibrahim, Zienab A.; Hamad, Sahar A. B.; Finnegan, Gary (Frontiers in Public Health, 2021)
Objective: This study aims to explore vaccine information-seeking behavior and its determinants among pregnant women in Khartoum state, Sudan. The findings from this study will be used to inform further development of policies and interventions in Sudan to increase vaccine acceptance and demand. Methods: A hospital-based cross-sectional study was conducted in two public hospitals, Omdurman maternity and AL-Saudi hospitals in Omdurman, Khartoum state, from February to April 2020. Results: We interviewed 350 pregnant women in the two hospitals. Our findings showed that one-third of pregnant women (35.7%) searched for information about vaccines. The vast majority searched for this information before pregnancy and during pregnancy (34.4% and 59.2%, respectively). They primarily searched for topics related to vaccine schedules and vaccine side effects (28.8% for each). The main source of vaccine-related information consumed by pregnant women were health care professionals, particularly doctors (40%), as well as the internet (20.8%). Findings showed that a high level of education was associated with a greater likelihood of searching for additional vaccine information. Moreover, those who perceived their family to have a high income were more likely to search for information. Additionally, pregnant women with low confidence in vaccines were more likely to be involved in searching for additional vaccine information. This highlights the need for high-quality, easily accessible information that addresses their needs. Conclusion: our findings showed that confidence in vaccine influences seeking for relevant information. We recommend the development of client-centered communication interventions to help increasing vaccine confidence and consequently vaccine acceptance and demand.